Leveraging undergraduate learning assistants when implementing new laboratory curricula - Griffin, James H.; Thompson, Jordan C.; López, Pía A.; Link, Renée D. (Frontiers in Education, 2024)
At University of California, Irvine, a large-enrollment research university, undergraduate chemistry courses for non-chemistry majors were delivered remotely during the 2020-2021 academic year, with a return to in-person instruction planned for January 2022. Because this return to in-person instruction coincided with the transition of second-year students from general chemistry to organic chemistry laboratory courses, the instructional staff recognized a need for remedial laboratory curricula for students with no prior in-person laboratory experience. Simultaneously, we desired to implement undergraduate Learning Assistants (LAs) in non-chemistry major organic chemistry laboratories for the first time at our university. In this paper, we describe our approach for leveraging undergraduate LAs to (1) test new laboratory curricula and (2) address feelings of comfort and safety for students with no prior in-person laboratory experience. Benefits of our LA program perceived by students include increased laboratory efficiency and improved student learning from near-peer instructors; benefits perceived by LAs include the development of professional skills and teamwork with graduate student teaching assistants. We provide an outline of resources and strategies to enable instructors to simultaneously implement undergraduate LAs and new laboratory curricula.